PENGARUH PERTUMBUHAN PENDAPATAN, ASET TETAP KOTOR, UKURAN PERUSAHAAN, DAN IMBALAN PASCAKERJA YANG DIMEDIASI OLEH TAX AVOIDANCE TERHADAP PERSISTENSI LABA (STUDI EMPIRIK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2011-2015) - Michele Alodia Jovita; Timbul Simanjuntak (Jurnal Riset Akuntansi dan Bisnis, 2017)
This research aims to identify the factors that affectedtax avoidance andanalyze the effect of tax avoidance on the earnings persistence of manufacturingcompanies listed on the Indonesia Stock Exchange from 2011 until 2015. Sampleswere taken by the purposive sampling method, with the criteria as follows: (1) themanufacturing companies listed on Indonesia Stock Exchange during the period2011 until 2015, (2) they published their financial statements per December 31which has been audited from 2011 until 2015, (3) they have positive profit in thecurrent years, (4) they have positive revenue growths, and (5) they have all dataneeded in this research completely. The method used is path analysis test. Theresults showed that before the existence of moderation variables, partially, all thevariables have positive effect on earnings persistence, except gross fixed assets.While after there is tax avoidance as a moderation variable, revenue growth andgross fixed assets have negatife influence towards earnings persistence; butmediation influence exists only on gross fixed assets and firm size. Meanwhile,revenue growth, gross fixed assets, firm size, and post-employment benefitssimultaneously affect earnings persistence, with or without tax avoidance asmoderating variables in manufacturing firms listed on the Indonesia StockExchange during the period 2011 to 2015.